Avaliação da morfologia, volume e área de maior constrição da via aérea superior posterior em pacientes classes II de angle submetidos à cirurgia ortognática bimaxilar - Scolari, Neimar (2019)
The treatment of dentofacial deformities by bimaxillary orthognathic surgery performing advancement and rotacion movements of the maxillomandibular complex has developed in recent years due to the appearance of computed tomography. This exam analyses different structures by the tomographic sections in different planes, both pre and postoperative. One of these structures is the posterior airway. This structure suffers changes, and it is described in the patients that perform this type of surgery. However, there is a need for new studies.The surgical movements performed by the surgery modify hard and soft structures reflecting as favourable or not favourable changes in the regions of the pharyngeal air space, and its different segments (nasopharynx, oropharynx, and hypopharynx). These changes are predicted from adequate planning using software loaded with computerized tomography Cone Beam. The software used in this study for this purpose was Dolphin Imaging 11.9v. It was analyzed the effects on morphology, volume, and area of upper posterior airway constriction on maxillomandibular advancement on 25 patients classified as Angle Class II, who underwent orthognathic surgery to correct the skeletal and dental discrepancy.Two scientific papers described the objectives of this study. The article 1 evaluated the volume alterations, and the minimal axial area of the upper posterior airway related to the sagittal plane of the face in the three specific regions of this airway: nasopharynx, oropharynx, and hypopharynx. Contrariwise, the article 2 evaluated the morphological alterations of the area of upper posterior airway constriction in the pre and postoperative. The results showed significant increases in the total pre and postoperative oropharyngeal, and hypopharyngeal volume. When the variable analyzed is the area of airway constriction, there are significant increases in the total area, and also in the oropharynx area. A comparison of this variable with the morphology (graphic form) of the airway from the axial cuts suggests that the cylindrical and trapezoidal shape may be more permeable, contributing positively to the improvement of the patient's respiratory complaints after orthognathic surgery. Besides, the trapezoidal anatomy of medial and spherical constriction would be associated with postoperative respiratory obstructions.